New perspectives on Rosa Luxemburg's concept of the transition to socialism. (October 2021) - Hudis, Peter
The ongoing project to issue the Complete Works of Rosa Luxemburg, which will make all of her writings available in English translation, provides a critical lens to re-evaluate aspects of Luxemburg's theoretical contribution that has often been passed over in much of the secondary literature on her. Of foremost importance in this regard is the distinctive contribution that she made to the understanding of how to achieve a transition to socialism in a developing society that remains surrounded by the capitalist world market and imperialist powers. This paper aims to show that her reflections during and after the 1905 Revolution, especially as reflected in a series of rarely studied articles and essays in the Polish revolutionary press, provides an important corrective to how the transition to socialism was understood by other Marxist currents.